Feasting our eyes on the candidates: visual cues in televised debates prime personality traits of lesser known candidates and promote learning - Nina, S. R.; Santana-Pereira, J. (International Journal of Press-Politics, 2021)
This article examines how different modes of exposure to debates between presidential candidates affect both the criteria by which they are assessed and levels of learning about politics in an unobtrusive, distant context. In this study, 167 Portuguese undergraduate students were randomly assigned to either watch or listen to one of two 1986 dyadic presidential debates, rate the candidates on a series of items, and answer questions about the contents of the debate. We found that the mode of exposure only affected the assessment criteria of the lesser known presidential candidate. In fact, his personality appraisals carried more weight for viewers than for listeners, while the substantive performance was more important for those who listened to the debate. Although a more confrontational debating style lowered the ratings of the lesser known candidate, this was not conditional to mode of exposure. Moreover, video exposure to the debate resulted in higher levels of learning. In summary, this study supports the assumption that the visual cues in audiovisual formats are major factors of learning and prime personality traits as criteria for the appraisal of (relatively) unknown candidates.